Shield Construction Effect on the Existing Subway Tunnel Structures and Efficiency of Grouting Reinforcement Measures: a 3D Model and a Case Study - Zhengya ZHANG; Bohao LI; Yong YAN; Jinwei FU; Hadi HAERI; Vahab SARFARAZI (Medžiagotyra)
The impact of shield construction on existing structures is analyzed, and the effectiveness of various reinforcement measures is compared using Midas GTS NX software. The use of isolation piles and sleeve valve pipe grouting as reinforcement measures is evaluated to determine their effects on mitigating uneven settlement and horizontal displacement of existing buildings. The analysis shows that advance grouting effectively controls the settlement caused by excavation, stabilizing vertical deformation of the bottom plate to within ±1.5 mm throughout the construction phase. In contrast, in-hole compensation grouting limits this settlement to within ±1 mm. Additionally, it is noted that in the intersection area of the bottom plate, the reverse bending of the bottom longitudinal beam may result in a slight uplift.